Gamma knife radiosurgery for uveal melanoma: 12 years of experience. Issue 1 (29th August 2008) - Modorati, G; Miserocchi, E; Galli, L; Picozzi, P; Rama, P
Abstract : Aim: To present our treatment protocol and evaluate the results of Gamma knife radiosurgery (GKR) in treating patients with uveal melanoma. Methods: Seventy-eight consecutive patients with uveal melanoma underwent stereotactic radiosurgery (radiation dose 30–50 Gy) with a Leksell Gamma-Knife at the San Raffaele University Hospital, Milan, Italy between 1994 and 2006. The main outcome measures evaluated were: survival rate, local tumour control, eye retention rate, visual acuity and treatment-related complications. Results: Survival rate was 88.8% at 3 years and 81.9% at 5 years. Local tumour control was achieved in 91.0% of patients. The median tumour thickness reduction after treatment was 1.96 mm (p<0.0001) (−32.1%). The eye retention rate was 89.7%. A significant relative reduction of visual acuity was observed during follow-up. The most frequent treatment-related complications were: exudative retinopathy (33.3%), neovascular glaucoma (18.7%), radiogenic retinopathy (13.5%) and vitreous haemorrhages (10.4%). Conclusion: GKR can be considered an alternative to enucleation for the treatment of choroidal melanomas.